Mathematical formulation of a modified film thickness equation for multipad externally adjustable fluid film bearing. Issue 1 (1st January 2018) - Hariharan, Girish; Pai, Raghuvir
Abstract: High-speed turbomachinery applications demand a highly stable spindle support system with a need for hydrodynamic bearings with better performance and stability characteristics. The multipad adjustable bearing geometry proposed in this study offers a unique attribute of altering the film thickness in the bearing clearances. The adjustability principle is applied to the four circumferentially spaced bearing pads or elements to translate in radial and tilt directions. The proposed bearing design provides an efficient alternative in the field of active journal bearings. This paper presents a geometrical approach employed in formulating a theoretical equation for film thickness variation under different pad adjustments. The mathematical relation for film thickness is derived using certain trigonometric relations by considering both the radial and tilt adjustment parameters. The present approach provides an accurate approximation of circumferential film thickness variation for an adjustable bearing in comparison with other film thickness models.